General principles of law and taxation - Lasiński-Sulecki, Krzysztof; Morawski, Wojciech; Prejs, Ewa (Review of European and Comparative Law, 2022)
Although the general principles of law at first sight do not bring about numerous associations with the sphere of taxation where the processes of compliance with legal rules or applying them must end with a precise numerical result, both the relevance and the significance of these principles in the sphere of tax law are more and more noticeable. The principle of proportionality has been invoked in probably every second VAT judgment of the Court of Justice for years. The principle of legal certainty has made its way to the case law of the said court as well as the Constitutional Tribunal in Poland. The importance of other principles is definitely on the rise.